Interaksionisme Simbolik dalam Moderasi Dakwah KH. Ahmad Mustofa Bisri di Instagram - Najichatun Nur Zana; Mansur Hidayat (Bulletin of Indonesian Islamic Studies, 2023)
The digital era encourages Kiai to convey da'wah messages through Instagram. This study describes the symbolic interactionism that occurs in the moderation of KH. Ahmad Mustofa Bisri’s da’wah on Instagram. The study was conducted on the Instagram account of @s.kakung managed by KH. Ahmad Mustofa Bisri. The analytical method uses qualitative data collection techniques utilizing observation, notes, and documentation. The results of this study show that: First, the concept of moderation of da'wah uploaded by KH. Ahmad Mustofa Bisri consists of three symbols, namely: the display of pictures, the display of videos, and the display of writing related to national commitment, respect for local culture, love of the motherland, faith in Allah, love of peace, and being forgiving. Second, in general, the symbolic interactionism that occurs between KH. Ahmad Mustofa Bisri and his followers can be divided into three parts, namely: Mind occurs when KH. Ahmad Mustofa Bisri and his followers understand each other what they are talking about. Self occurs when followers respond by liking posts or leaving comments. Meanwhile, society occurs when followers can actualize the influence gained daily.